Influencia de bajos ingresos económicos en la generación de estrés por Covid 19 en los estudiantes de IV Ciclo de las Escuelas Historia y Arqueología - Universidad Nacional de Trujillo, 2021 - Villacorta Radas, Adria Cristina (2022)
The purpose of this thesis is to analyze the influence of low economic income on the generation of stress by Covid 19 in IV Cycle students of the History and Archeology Schools - National University of Trujillo, 2021. The type of descriptive - qualitative research has been considered, working with two schools, the School of History, which has a total of 12 students, and the School of Archeology, with 18 students, being a mixed approach. The investigation has been carried out with students who have the same problem and a sample of 28 students was taken from both schools, reflected in the testimonies that the interview allowed to know the experiences lived by the students; and methods such as inductive, deductive and statistical were put into practice, in addition techniques such as the survey and the interview were applied to obtain quantitative and qualitative data respectively. This research is relevant for Social Work, because it is a topic that generates an impact for our professional intervention, in order to sensitize parents, students and authorities, to work in a coordinated manner and recognize the importance of stability. physical, spiritual and mental in families. This thesis is subdivided into: I. Introduction: the problematic reality, background, theoretical bases and conceptual framework are deepened; II. Materials and methods for the collection of statistical data and techniques and instruments; III. Results presentation; IV. Discussion of results; V. Conclusions; SAW. Bibliographic references, Annexes.